Effects of chronic lithium administration on renal acid excretion in humans and rats. Issue 12 (11th December 2014) - Weiner, I. David; Leader, John P.; Bedford, Jennifer J.; Verlander, Jill W.; Ellis, Gaye; Kalita, Priyakshi; Vos, Frederiek; de Jong, Sylvia; Walker, Robert J.
Abstract Lithium therapy's most common side effects affecting the kidney are nephrogenic diabetes insipidus (NDI) and chronic kidney disease. Lithium may also induce a distal renal tubular acidosis. This study investigated the effect of chronic lithium exposure on renal acid–base homeostasis, with emphasis on ammonia and citrate excretion. We compared 11 individuals on long‐term lithium therapy with six healthy individuals. Under basal conditions, lithium‐treated individuals excreted significantly more urinary ammonia than did control subjects. Following an acute acid load, urinary ammonia excretion increased approximately twofold above basal rates in both lithium‐treated and control humans. There were no significant differences between lithium‐treated and control subjects in urinary pH or urinary citrate excretion. To elucidate possible mechanisms, rats were randomized to diets containing lithium or regular diet for 6 months. Similar to humans, basal ammonia excretion was significantly higher in lithium‐treated rats; in addition, urinary citrate excretion was also significantly greater. There were no differences in urinary pH. Expression of the critical ammonia transporter, Rhesus C Glycoprotein (Rhcg), was substantially greater in lithium‐treated rats than in control rats. We conclude that chronic lithium exposure increases renal ammonia excretion through mechanisms independent of urinary pH and likely to involve increased collecting duct ammonia secretion via the ammonia transporter, Rhcg.